Mus musculus (Linnaeus, 1758) Immune Responses Caused by Escherichia coli (Migula, 1895) Infection - Mitasari, Zuni; Gofur, Abdul; Listyorini, Dwi (KnE Life Sciences, 2017)
Escherichia coli (Migula, 1895) is a negative gram bacteria which have an ability to cause some deseases, such as meningitis, urinary tract infection and digestive tract infection. Lipopolysaccharide (LPS) in its cell wall induces immune responses in many ways. The objective of this study was to investigate the effect of E. coli infection on lymphocyte numbers and spleen weight in mice [Mus musculus (Linnaeus, 1758)]. Twenty five male mice were grouped into negative control, positive control group treated with PBS, and three experimental groups injected intraperitonially with E. coli 1.5 × 103 cfu/mL,1.5 × 105 cfu/mL or 1.5 × 107 cfu/mL respectively. About 5 d after the injection, the spleen were collected. Spleen were weighed using digital balance, number of lymphocyte were counted using hemocytometer. E. coli infection significantly increase both weight of the spleen and number lymphocyte. In conclusion, mice responded to E. coli infection by increasing the number of its lymphocyte. Keywords: Escerechia coli (Migula, 1895); immune respone; infection; Mus musculus (Linnaeus, 1758).